Knowledge sharing and its impact on the strategic renewal of the tourism industry in Iraq (a survey of the Tourism Authority) - JALEL AZiZ, HAGER; HAMID JAMAL, DINA (International Journal of Psychosocial Rehabilitation, 2020)
The current study aims to demonstrate the extent to which the influence relationship of the study variables has been achieved, knowledge sharing in the strategic renewal of a sample of leaders in the tourism authority in Baghdad, by analyzing the opinions of a sample in the tourism authority and by (120) questionnaires distributed among (general managers, and assistants of general managers, Department heads, division officials) and the study included the relationship between cognitive sharing as an independent variable and strategic renewal as a dependent variable, and the first variable included three sub-dimensions (individual, organizational, and technological), while the second variable included three sub-dimensions that included (context, content the process), and these variables have interacted to form the general framework around which a study revolves, as the main and subsidiary hypotheses have emerged in order to reach the goal of the study mentioned above.